Immediate knowledge according to Al-Qāá̧oeī ê¿abd Al-Jabbār - Mohd Radhi Ibrahim (Cambridge University Press, 2024)
Since Ibn Mattawayh and Mānkdīm up until George Hourani and Marie Bernand, there is an unstoppable interest among scholars towards Ê¿Abd al-Jabbār theory of knowledge. This interest has increased after the publication of the works of the late MuÊ¿ tazilites such as Kitāb al-MuÊ¿tamad fī Uá£ūl al-Dīn of Ibn al- Malāá̧¥imī and Kitāb Taá£ affuá̧¥ al-Adilla of his teacher Abū al- á̧usayn al-Baá£rī. This article seeks to examine Ê¿Abd al-Jabbār's theory of immediate knowledge based on his Mughnī and other sources from his students and the late MuÊ¿tazilites. I will also examine the implication of Ê¿Abd al-Jabbār's view on immediate knowledge on his theological arguments. This article is divided into two divisions; firstly, I will study the definition of immediate knowledge according to Ê¿Abd al-Jabbār and the responses from his successors. Secondly, I will analyze his view on the types of immediate knowledge that closely related to his theological arguments. From this point of view I will indicate that the disagreement about the content of immediate knowledge will lead to the dispute on the theological arguments among Muslim theologians (mutakallimūn).